Understanding the patterns of technology and internet use for academics by undergraduate medical students in a teaching hospital of North India - Sneha Mohan; Sumit Malhotra (Wolters Kluwer Medknow Publications, 2019)
Background: E-learning or computer-based learning has been incorporated into medical education in many countries. Readiness to utilize this medium merits exploration in the Indian context. Therefore, we aimed at assessing the current patterns of technology and internet use by undergraduate medical students in a tertiary care teaching hospital, focusing on their use for academics and their views on e-learning. Materials and Methods: This cross-sectional study was conducted using a self-administered questionnaire among undergraduate medical students in the first 4 years of the study. The data generated were entered into Microsoft Excel and analyzed using SPSS version 22. Descriptive analysis and comparison of proportions were done using Chi-square test. Results: A total of 212 students responded, with a mean (±standard deviation) age of 20 years (±1.54) and 70.3% of males. There was universal access to technological devices with complete internet access. Internet was used primarily for entertainment (99.1%) and WhatsApp (97.2%), with 86.8% use in academics. Most students accessed the internet multiple times each day. Majority of the students (90.6%) used social networking sites and were open to using it for academics. Reliability of the material found online was a concern (83.5%), and most (63.2%) were interested in further training. Only a quarter of the students had utilized medical e-learning material online, and a majority (77.4%) were willing to incorporate it into the curriculum feeling that it would benefit them (64.6%). Conclusions: Incorporating e-learning tools into the medical curriculum needs to be considered for undergraduate medical studies, owing to its availability and readiness for utilization.